2021
DOI: 10.1186/s40249-021-00920-6
|View full text |Cite
|
Sign up to set email alerts
|

Current efforts towards safe and effective live attenuated vaccines against African swine fever: challenges and prospects

Abstract: Background African swine fever (ASF) is a fatal hemorrhagic disease in domestic pigs and wild boar caused by African swine fever virus (ASFV). Since ASF has been introduced into Europe and Asia, the major pig-raising areas, posing a huge threat to the pork industry worldwide. Currently, prevention and control of ASF are basically dependent on strict biosecurity measures and stamping-out policy once ASF occurs. Main text The major risks of ASF sprea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…The development of safe and effective vaccines is one of the key strategies. In order to generate attenuated ASF vaccines, virulent ASFV strains have had several virulence-associated genes deleted, such as I177L, 9GL, UK, EP402R (CD2v), DP148R, A238L, MGF505, MGF360, etc., and have shown decreased virulence and high efficacy to protect pigs infected with their parental strains [ 24 , 39 , 40 ]. Scientists from China and the United Kingdom have reported that the ASFV strains, which were deleted the MGF505 and MGF360 genes or the MGF505, MGF360 and EP402R (CD2v) genes, greatly attenuated their virulence and protected pigs from challenges with their parental trains [ 24 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The development of safe and effective vaccines is one of the key strategies. In order to generate attenuated ASF vaccines, virulent ASFV strains have had several virulence-associated genes deleted, such as I177L, 9GL, UK, EP402R (CD2v), DP148R, A238L, MGF505, MGF360, etc., and have shown decreased virulence and high efficacy to protect pigs infected with their parental strains [ 24 , 39 , 40 ]. Scientists from China and the United Kingdom have reported that the ASFV strains, which were deleted the MGF505 and MGF360 genes or the MGF505, MGF360 and EP402R (CD2v) genes, greatly attenuated their virulence and protected pigs from challenges with their parental trains [ 24 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a DIVA strategy is essential. Two DIVA strategies for ASF LAVs have been discussed in the recent literature, one a multiplex real-time PCR targeting both the p72 gene of the wild-type ASFV strain and the deleted gene(s) of the LAV, the other the detection of antibodies induced by the deleted gene-encoded protein by enzyme-linked immunosorbent assay (ELISA) [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…This approach is being developed to improve the safety profile of naturally attenuated strains and for the attenuation of circulating virulent strains. Thus far several genes have been targeted: the hemagglutinin CD2v/EP402R, the thymidine kinase TK/K169R, the NF-κβ and NFAT inhibitor A238L, the apoptosis inhibitors A179L and A224L, the protein phosphatase-1 activator NL/DP71L, the genes involved in inhibiting the induction of Type I interferons such as MGFs 360 and 505 and the non-homologous I329L, K205R, DP148R and A276R, and genes implicated in the virulence of different ASFV virulent strains but whose mechanism of action is unclear, including 9GL/B119L, UK/DP96R, I177L, I226R, A137R, and E184L [ 8 , 51–53 ]. However, rational deletion does not always produce the intended result.…”
Section: Asf Vaccine Approachesmentioning
confidence: 99%
“…Since then it spread to more Asian countries, including Vietnam, Cambodia, North Korea, Laos, Indonesia, Myanmar, Philippines and South Korea [ 17 19 ]. No commercial vaccines and effective treatments are available to control the disease [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%